Bingkai pemberitaan mundurnya wolfgang pikal dari kursi pelatihan persebaya pada kompas.com, liputan6.com, dan jawapos.com - Bhimantara, Edo Satriya; Christantyawati, Nevrettia (Soetomo Communication and Humanities, 2020)
This study aims to find out what is in the news on social media by using framing analysis. The media used were Kompas.com, Liputan6.com and JawaPos.com media in reporting Wolfgang Pikal to resign from the Persebaya training chair. This study focused on the poor performance that occurred in Persebaya in the last six matches and the factors that caused the decline in Persebaya's performance. Through framing analysis of Zongdan Pan and Kosicky methods with several elements, namely syntax, scripts, thematic, and rhetorical. And using Ralf Dahrendof's conflict theory with several elements, namely capital decomposition, labor decomposition and the emergence of a new middle class as a unit of analysis in the discussion This study shows that the media as a reflection of reality. the results of this study will show how the media presents a picture of the news that has been loaded on social media.Keywords:Â framing, performance, conflict, reality reflection, supporters.Â